2015
DOI: 10.14260/jemds/2015/108
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Pefr and MVV Between Indian Born Tibetan Youths and Indian Youths

Abstract: BACKGROUND AND OBJECTIVE: Tibetans are the oldest population living permanently at high altitude (4000m). This ethnic group along with Sherpas may have been living at high altitude for longer than any other population. Previous research has shown Tibetans living at high altitude to have superior pulmonary functions. The size of the lungs relative to the size of the person varies depending on ethnic group and a host of environmental factors. Peak expiratory flow rate (PEFR) measurement is the easiest and cheape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The PEFR measurement delineates the physiological function of large airways and it decreases when there is moderate to severe airway obstruction. Further, PEFR measurement displays a significant association of the clinical course of asthma with pulmonary functions and it elicits an early sign of deteriorating lung function and is thus helpful for appropriate treatment and good patient outcomes [ 22 ]. The measurement of MVV assesses the complete function of the respiratory system, including the respiratory muscles, airway resistance, and the compliance of the lungs and chest wall [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEFR measurement delineates the physiological function of large airways and it decreases when there is moderate to severe airway obstruction. Further, PEFR measurement displays a significant association of the clinical course of asthma with pulmonary functions and it elicits an early sign of deteriorating lung function and is thus helpful for appropriate treatment and good patient outcomes [ 22 ]. The measurement of MVV assesses the complete function of the respiratory system, including the respiratory muscles, airway resistance, and the compliance of the lungs and chest wall [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, PEFR measurement displays a significant association of the clinical course of asthma with pulmonary functions and it elicits an early sign of deteriorating lung function and is thus helpful for appropriate treatment and good patient outcomes [ 22 ]. The measurement of MVV assesses the complete function of the respiratory system, including the respiratory muscles, airway resistance, and the compliance of the lungs and chest wall [ 22 ]. Similarly, in our study, there is a significant decline in observed value for PEFR (4.76 ± 0.42 vs. 5.82 ± 0.65; p = 0.03) and MVV (78.65 ± 28.45 vs. 115.87 ± 32.15; p = 0.001) as compared to the predicted value.…”
Section: Discussionmentioning
confidence: 99%